Prevalence of Decreased Bowel Movements in Tracheostomy Patients in a Tertiary Care Hospital - Hashmi, Syed Qasim; Naeem, Shawaf; Zia, Sadaf; Rashid, Hira; Shahid, Abdul Hadi; Jamil, Afifa (Biological and Clinical Sciences Research Journal, 2025)
Tracheostomy alters laryngeal mechanics and may impair the Valsalva manoeuvre, predisposing patients to decreased bowel movements and constipation. Evidence on constipation using the Rome IV criteria in adult tracheostomy patients is limited. Objective: To determine the prevalence of Rome IV–defined constipation and describe bowel symptoms among adult tracheostomy patients in a tertiary-care setting. Methods: This single-centre prospective study enrolled consecutive adults (≥18 years) who underwent tracheostomy at the Otorhinolaryngology Department, Dow University of Health Sciences & Dr. Ruth K. M. Pfau Civil Hospital, Karachi, Pakistan, from March to May 2025. Patients had a tracheostomy in place for≥30 days; those with prior gastrointestinal disorders, constipation secondary to medications, current laxative use, or ICU/vegetative state were excluded. Participants completed a questionnaire at 1-month follow-up, capturing demographics and Rome IV items. Categorical variables were compared with Chi-square tests and continuous variables with independent-samples t-tests (α=0.05). Results: Ninety-five patients were included (mean age 51.9 ± 15.6 years; 78.9% male). Prior constipation was reported by 3.2% (n=3); none were on constipation medications, and none had colon or neurological disease. Overall, 91.5% reported hard stools in the prior two weeks; 57.9% had hard stools in ≥50% of defecations; 71.6% strained in >25% of defecations; 29.4% reported incomplete evacuation in >25%; 29.5% experienced anorectal obstruction in 25%; 11.6% required manual evacuation; and 86.3% had <3 Spontaneous bowel movements/week. Rome IV constipation prevalence was 71.6% (68/95). Compared with non-constipated patients, the constipated group more often had hard stools ≥50% (100% vs 0%), straining >25% (100% vs 0%), anorectal obstruction 25% (41.2% vs 0%), manual evacuation (16.2% vs 0%), and precisely two bowel movements/week (95.6% vs 51.9%) (all p<0.001 except manual evacuation p=0.030). Age did not differ significantly (51.1 ± 15.7 vs 53.9 ± 15.4 years; p=0.439). Conclusions: Constipation by Rome IV criteria is highly prevalent (72%) one month after tracheostomy in this tertiary-care cohort, despite minimal prior diagnoses. Routine screening and early bowel regimens (including hydration, fibre, mobilization, and laxatives as indicated) should be integrated into post-tracheostomy care pathways. Multicentre, longer-term studies are warranted to confirm these findings and identify modifiable risk factors.